Pemikiran Hukum Islam Ibn Taimiyah tentang Akad Nikah Tanpa Lafaz Kabul - Rohim, M. Yusuf Nur; F, Fatmawati; Sultan, Lomba (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Marriage is the best way to build a Muslim family which is nothing but a strong foundation in building an ideal society. The marriage contract is considered the most important contract in human life. It is also a foundation in a person's life, which should not be underestimated. So it needs caution and accuracy in it, so that it is in line with the sincere intentions and sense of responsibility of the person who runs it. Islam has set all the foundations and values that must be contained in this marriage, which aims to maintain its position and influence in human life. This study aims to explain the definition and pillars of marriage, especially lafaz ijab kabul, as well as Ibn Taymiyah's views on the marriage contract without lafaz ijab kabul.